PENGARUH PENGENCERAN DAN PENGADUKAN LIMBAH DAPUR DAERAH NGESREP TERHADAP PENINGKATAN PRODUKSI BIOGAS DENGAN MENGGUNAKAN EKSTRAK RUMEN SAPI SEBAGAI STARTER - Mohammad Rama Fadillah Soeroso; Sudarno Sudarno; Irawan Wisnu Wardhana (Jurnal Teknik Lingkungan, 2013)
The increase of oil prices affects economic activity in the world including Indonesia, it would encourage the government to develop renewable energy including biogas. Kitchen wastes have the potential to be a source of renewable energy, namely biogas. Food waste and kitchen activities in sufficient quantities from the cafeteria collected, and treated such as refining and homogenizing, then enter a stage of the substrate and its extracts as a source of rumen anaerobic bacteria into the batch reactor with the addition of water as a variation. From the results of the study concluded that the addition of water affects the amount of gas produced. It is proven through the reactor which produces biogas most is reactor with 150 ml dilution (A) (pieces shape) which were stirred three times a day, this reactor is capable of producing up to 1394 ml within 24 days. Based on the time of production, the level of water and mixing also affects the length of time in the production of biogas. Biogas production without a stirring process is capable of producing biogas up to 19-20 days, while the stirred reactor were capable of producing biogas up to 25-26 days.